Molecular cloning, sequencing, and mapping of EGR2, a human early growth response gene encoding a protein with "zinc-binding finger" structure. - Joseph, L J (1988)
Early growth response gene-1 (Egr-1) is a mouse gene displaying fos-like induction kinetics in diverse cell types following mitogenic stimulation. Egr-1 encodes a protein with "zinc-binding finger" structure. Zinc fingers are a protein structural motif that serve as DNA-binding domains in several transcriptional regulatory proteins. Using low-stringency hybridization with an Egr-1 cDNA probe, we identified a distinct human cDNA (designated EGR2 for early growth response gene-2), which is coregulated with EGR1 by fibroblast and lymphocyte mitogens; however, several stimuli that induce Egr-1 mRNA in PC12 (rat pheochromocytoma) cells do not induce Egr-2 mRNA. The cDNA sequence predicts a protein of 406 amino acids, including three tandem zinc fingers of the Cys2-His2 class. Strikingly, the deduced amino acid sequences of human EGR2 and mouse Egr-1 are 92% identical in the zinc finger region but show no similarity elsewhere. EGR2 maps to human chromosome 10 at bands q21-22. Structure-function analysis of EGR2 and EGR1 proteins should provide insight into the mechanisms linking signal transduction and transcriptional regulation of gene expression.